Analisis Faktor-Faktor Yang Mempengaruhi Ekspor Kerajinan Perak Di Provinsi Bali - Suardani, Ni Luh Anik; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
One of the art products from Bali are attractive to tourists and has become one of the export products, especially in the field of handicrafts namely silver. This study aims to determine the effect of the amount of labor, production and foreign exchange rates simultaneously and partially effect on the export of silver in Bali Province. The data used secondary data. Data collection method used the case study method. The analysis technique used in this research is multiple linear regression analysis. The results of the analysis of obtained results of labor, production, and exchange rate simultaneously significant effect on the export of silver in Bali Province. Partially amount of production and the dollar exchange rate and a significant positive effect on exports of silver in Bali Province. Meanwhile, a partial amount of labor does not affect the export of silver in Bali Province .